2014
DOI: 10.1021/jp5054315
|View full text |Cite
|
Sign up to set email alerts
|

Crystallinity Effects in Sequentially Processed and Blend-Cast Bulk-Heterojunction Polymer/Fullerene Photovoltaics

Abstract: Although most polymer/fullerene-based solar cells are cast from a blend of the components in solution, it is also possible to sequentially process the polymer and fullerene layers from quasi-orthogonal solvents. Sequential processing (SqP) not only produces photovoltaic devices with efficiencies comparable to the more traditional bulk heterojunction (BHJ) solar cells produced by blend casting (BC) but also offers the advantage that the polymer and fullerene layers can be optimized separately. In this paper, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
74
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 47 publications
(75 citation statements)
references
References 97 publications
1
74
0
Order By: Relevance
“…We also explore how our design rules apply to highly crystalline polymers such as P3HT when the degree of fi lm crystallinity is controllably varied. [ 57 ] Thus, the SqP design rules we establish here open up an entire new avenue of morphology control in processing polymer:fullerene BHJ photovoltaics.…”
Section: (2 Of 11)mentioning
confidence: 93%
See 3 more Smart Citations
“…We also explore how our design rules apply to highly crystalline polymers such as P3HT when the degree of fi lm crystallinity is controllably varied. [ 57 ] Thus, the SqP design rules we establish here open up an entire new avenue of morphology control in processing polymer:fullerene BHJ photovoltaics.…”
Section: (2 Of 11)mentioning
confidence: 93%
“…[ 57 ] In particular, we found that as we decreased the P3HT crystallinity, traditional blend-cast devices had their performance suffer, but the performance of sequentially-processed devices improved because there was more swelling of the polymer underlayer leading to better fullerene intercalation and photocurrent. [ 57 ] We therefore conclude that porosimetry-ellipsometry measurements can be used to understand-and thus ultimately manipulate-the extent of fullerene intercalation into polymer/fullerene active layers produced by SqP. Hence, by controlling the degree of underlayer swelling, [ 57 ] SqP offers a more rational route to polymer:fullerene BHJ formation.…”
Section: Using Porosimetry-ellipsometry To Quantify Conjugated Polymementioning
confidence: 96%
See 2 more Smart Citations
“…All of these features lead to the excellent electrical properties of these materials [6,7]. Recently, many interesting reports on SqSD-processed polymer/fullerene OPVs based on P3HT and fullerene derivatives have been reported [4,5,[8][9][10][11][12][13][14][15]. However, similar to a BSD-processed P3HT/fullerene OPVs, SqSD-processed P3HT/fullerene OPVs require a thermal annealing step to obtain a satisfactory heterojunction area.…”
Section: Introductionmentioning
confidence: 99%